O-021 Endovascular treatment significantly improves outcomes compared to IV thrombolysis for strokes secondary to large vessel occlusions. 8-year experience. (4th July 2012) - Rai, A; Carpenter, J; Roberts, T; Rodgers, D
Abstract : Introduction: New thrombectomy devices for acute ischemic stroke (AIS) may allow endovascular therapy (EVT) to gain traction. However for EVT to have a significant impact on stroke it has to demonstrate improved functional outcomes compared to the conclusively proven IV rt-PA (IVT) administration. Literature supports a higher efficacy of EVT for proximal vessel occlusions. The goal of the current undertaking was to compare EVT and IVT for AIS. Methods: We analyzed our prospectively maintained database of 425 patients for stroke treatments over an almost 8-year period. Only patients with a documented intracranial vascular occlusion in the anterior circulation on the baseline CTA who had undergone either EVT or IVT, but not both were included. A large vessel was defined as either the internal carotid artery terminus (ICA-T), the middle cerebral artery main stem with or without bifurcation involvement (M1) or isolated involvement of the proximal M2 branches (M2). A good clinical outcome was defined as mRS≤2. Results: 225 patients were anayzed (IVT=101, EVT=124). The baseline NIHSS of 16.1(±7.6) was not different between the two groups (p=0.9). Patients in the IVT-group were older (76.2±12.7 years) than the EVT-group (68.1±17.2 years), (p=0.0001). Lower baseline NIHSS (p<0.0001) and younger age (p<0.0001) predicted a good outcome. There was no difference in the percentage of ICA-T occlusions, 23.4% for EVT vs 17.5% for IVT (p=0.3). The EVT group had a significantly larger number of M1-occlusions compared to IVT, 56.5% vs 37.1% respectively (p=0.004) while there were a significantly larger number of M2- occlusions for IVT vs EVT, 45.4% vs 20.2% respectively (p<0.0001). The overall rate of good outcome was 36% while the mortality was 36.9%. Patients who underwent EVT had significantly higher good outcomes, (n=55, 44.4%) as compared to IVT (n=26, 25.7%), (p=0.003, OR 2.3, 95% CI 1.3 to 4.1). There was no difference in mortality between the two groups, 32.3% in EVT vs 42.6% in the IVT (p=0.1). For all occlusion sites, EVT resulted in significantly better outcomes than IVT. For ICA-T occlusions, a good outcome was seen in 27.6% for EVT vs 0% for IVT (p=0.004). For M1 occlusions, good outcome of 40% for EVT vs 10.5% for IVT (p=0.0007, OR-5.7, 95% CI 1.8 to 17.7) and for M2 occlusions, good outcome of 76% for EVT vs 47.8% for IVT (p=0.02, OR 3.4, 95% CI 1.2 to 10.2). A multi-variable logistic regression analysis was performed accounting for all significant predictors in the univariate analysis and especially controlling for the difference in age groups and occlusion-site composition between the two groups. This showed that accounting for all the variables, patients who underwent EV therapy had more than three times the odds of achieving a favorable outcome than those receiving IV thrombolysis (p=0.0007, OR 3.7, 95% CI 1.7 to 8.5). Conclusion: This large study of over 200 patients concludes that patients presenting with AIS secondary to a large vessel occlusion in the anterior circulation have significantly higher odds of a favorable outcome with EVT as opposed to IVT. Our data supports the rationale of a randomized trial with head-to-head comparison of EV vs IV therapy for large vessel occlusions. Competing interests: A Rai: Stryker Neurovascular. J Carpenter: Codman Neurovascular, Genetech. T Roberts: None. D Rodgers: None.